Prevalence of cytochrome P-450 2C9 (CYP2C9) alleles *2, and*3 among the Libyan population of Tripoli region - Shima, Hana; Elghawi, Laila; Kafu, Laila; Muhna, Kaltoom; Abud, Ayad; Bashein, Abdulla (Khalij-Libya Journal of Dental and Medical Research, 2025)
CYP2C9 gene encodes an enzyme that metabolizes a variety of drugs. Genetic variations in the CYP2C9 enzyme, particularly the CYP2C9*2 and CYP2C9*3 polymorphisms, can significantly impact enzyme activity, resulting in variations in drug metabolism and response among individuals who carry them. This study aimed to identify the prevalence of CYP2C9*2 and CYP2C9*3 alleles among the Libyan population in the Tripoli region and to compare the results with published data from other populations and ethnicities. This study included 300 randomly selected unrelated Libyan male blood donors, aged between 18 - 50 years. A high-resolution melting analysis (HRM) protocol was developed and employed as a screening tool for the detection of genetic variations, and direct DNA sequencing was used to confirm the presence of CYP2C9*2 and CYP2C9*3 polymorphisms. On one hand, 228 (73.33%) and 72 (24%) subjects were detected as wild-type and heterozygous CYP2C9*2, respectively, and on the other hand, 269 (98.66%), 29 (9.66%) and 2 (0.66%) subjects were detected as wild type, heterozygous and homozygous mutant CYP2C9*3, respectively. In conclusion, CY2C9*2 and *3 are prevalent in Libyans residing in Tripoli region.